The effect of hydro-alcoholic extract of Artemisia absinthium on appetite in male rats - Sara Baghban Taraghdari; Mohsen Nematy; Mohsen Mazidi; Maryam Kamgar; Mohammad Soukhtanloo; Mahmoud Hosseini; Hassan Rakhshandeh; Abdolreza Norouzy; Habibollah Esmaily (Mashhad University of Medical Sciences, 2015)
Objectives: weight loss as a consecution of losing appetite in post-operative patients and those suffering from HIV, cancer, cachexia and inflammatory diseases are the main inducements of morbidity and mortality. There is an increasing demand for more efficacious and endurable appetite stimulating treatment for patients with cachexia. Health economics is influenced by the malnutrition which was accounted for 5% of Iranian populations in 2011. Artemisia absinthium is known as an orexigenic herb in Iranian traditional medicine. Little evidence is available about its orexigenic effect and mechanism. So, the present study evaluated the possible effect on appetite of hydroalcoholic extract of Artemisia absinthium. Materials and Methods: Thirty male Wistar rats were randomly divided into five groups. Vehicle group received 0.5 ml water per day, control group did not receive anything and other 3 groups received 50, 100 and 150 mg/kg of Artemisia absinthium for 7 days respectively. The daily amount of the food eaten by each rat was measured for 10 consecutive days. The amount of energy intake for each rat was also calculated for 7 days during the intervention. The difference in energy intake was calculated and compared between groups. Results: The results suggest that there was no significant (p>0.05) differences in energy received before and during intervention between three case groups compared with the control group. The energy intake in 1-2 hours after extract injection in all groups, and energy intake after 24 hours interval in third case group (receiving 150 mg/kg extract) is higher compared to other intervals, but it is not significant (p>0.05). So, it can be stated that there was no significant differences between energy intake of 3 case groups and control group. Conclusion: Artemisia absinthium had no positive and dose-related effects on appetite of rats. Future studies are needed to evaluate the orexigenic effect of this plant.